1996
DOI: 10.1016/s0161-6420(96)30410-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Nerve Fiber Layer Thickness Measurements Using Optical Coherence Tomography

Abstract: Purpose-Optical coherence tomography (OCT) is a new technology that uses near-infrared light in an interferometer to produce approximately 10-μm resolution cross-sectional images of the tissue of interest. The authors performed repeated quantitative assessment of nerve fiber layer thickness in individuals with normal and glaucomatous eyes, and they evaluated the reproducibility of these measurements. Methods-The authors studied 21 eyes of 21 subjects by OCT. Each subject underwent five repetitions of a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
365
1
20

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 612 publications
(405 citation statements)
references
References 13 publications
19
365
1
20
Order By: Relevance
“…However, we found that the temporal RNFL thickness had a tendency to be thinner than the nasal quadrant. Similar to our results, observations between these two retinal areas that reached statistical significance, however, were described in works by Varma 32 and later reports by Schuman 23 and are also supported by histologic data. 33 We emphasize that there is a scarcity of published work on normal RNFL thickness using third-generation OCT. Because of its improved resolution, the anterior and posterior borders of RNFL are apt to be better defined.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we found that the temporal RNFL thickness had a tendency to be thinner than the nasal quadrant. Similar to our results, observations between these two retinal areas that reached statistical significance, however, were described in works by Varma 32 and later reports by Schuman 23 and are also supported by histologic data. 33 We emphasize that there is a scarcity of published work on normal RNFL thickness using third-generation OCT. Because of its improved resolution, the anterior and posterior borders of RNFL are apt to be better defined.…”
Section: Discussionsupporting
confidence: 93%
“…Our results of overall RNFL thickness and thickness measurements in particular retinal areas using the new generation OCT are consistent with previous reports using a default scan diameter of 3.4 mm from the center of the optic nerve head 23,[27][28][29] (RM Vessani, Retinal nerve fiber layer thickness measured by OCT3 and central corneal thickness in ocular hypertensive patients, ARVO 2004, paper #3407). The RNFL was thickest in the superior and inferior retinal areas and thinner in the temporal and nasal ones, which is in agreement with other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Detailed descriptions of the principles of OCT have already been published; a summary follows. [11][12][13][14][15][16][17][18][19][20][21][22][23] OCT is based on the principles of low coherence interferometry. By directing a low coherence light beam, which is analogous to a series of short pulses of light, onto a partially reflective mirror, two beams are created: reference and measurement beam.…”
Section: Oct Technologymentioning
confidence: 99%
“…7,8,[12][13][14] The reproducibility of ONH measurements using the Stratus OCT (Carl Zeiss Meditec, Dublin, CA, USA) was reported recently to be sufficient, especially regarding the cup-to-disc ratios (CDRs). 15 Although OCT may give objective measurement with less variation than biomicroscopy, this in itself does not mean that it will be more accurate in estimating the actual disc measurements.…”
Section: Introductionmentioning
confidence: 99%